The Relationship Between Teachers’ Art Experiences And Their Attitudes Towards The Importance Of Art Education In An International School In Bangkok, Thailand - Iglesias, Lemuel De Jose; Ye, Yan (Scholar: Human Sciences, 2019)
The purpose of this research was to identify teachers’ art experiences, as well as their attitudes towards the importance of art education, and subsequently determine the relationship between teachers’ experiences and their attitudes. The research focused on teachers from the primary level of an international school in Bangkok, Thailand. A questionnaire was used to gather information about teachers’ past art experiences as a student in primary, secondary school and university, as an adult and as related to family. Findings revealed that teachers value their art experiences in primary and secondary school as somewhat positive, while it was deemed neutral in university. A gradual change was also observed in the results regarding how teachers rated the importance of art education: from somewhat positive in primary and secondary school, to neutral in university. Correlation analyses further confirmed that there was indeed a significant relationship between teachers’ art experiences and their attitudes towards the importance of art education, particularly as a student.